An innovative longitudinal nurse-midwife mentorship program in rural Malawi: The Global Action in Nursing (GAIN) project - M. Openshaw; C. Kachimanga; I. Mphande; M. Sayenda; N. Mwale; E. Kapito; A. Blair; C. McMahon; M. Mhango; S. Rankin; K. Baltzell (Elsevier, 2023)
The Global Action in Nursing (GAIN) project is a partnership between University of California, San Francisco, Partners In Health, and the Ministry of Health, Neno District, Malawi that aims to reduce maternal and neonatal morbidity and mortality by improving the quality of perinatal care rendered by nurse-midwives. In this report, we describe the design and implementation of a nursing training and mentorship program for frontline nurse-midwives in leadership, quality improvement, and midwifery skills, including the implementation of the World Health Organization Safe Childbirth Checklist and Respectful Maternity Care. Short course trainings were followed by one year of on-site clinical mentorship with the goal of improving systems factors (such as ensuring adequate availability of supplies) as well as reinforcing clinical skills.The program was implemented in Neno District, Malawi, a rural district in southwestern Malawi where approximately 5,000 births occur annually. The program is now in its fifth year of implementation and has become well-embedded in the district. Key lessons learned included stakeholder involvement; flexible and responsive program design; nurse-centered model for mentorship; and program transition to local leadership. Since nurses and midwives are the frontline providers of reproductive health care in Malawi, sustained investment in clinical and leadership training for nurse-midwives, accompanied by health systems strengthening, has the potential to improve quality deficits and therefore the health of mothers and babies in low-resource settings.